2003
DOI: 10.1016/s1074-7613(03)00115-8
|View full text |Cite
|
Sign up to set email alerts
|

Competing Functions Encoded in the Allergy-Associated FcϵRIβ Gene

Abstract: Allergic reactions are triggered via crosslinking of the high-affinity receptor for immunoglobulin E, F(c)epsilonRI. In humans, F(c)epsilonRI is expressed as a tetramer (alphabetagamma(2)) and a trimer (alphagamma(2)). The beta subunit is an amplifier of F(c)epsilonRI surface expression and signaling. Here, we show that as a consequence of alternative splicing, the F(c)epsilonRIbeta gene encodes two proteins with opposing and competing functions. One isoform is the full-length classical beta, the other a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 64 publications
4
75
0
Order By: Relevance
“…One prediction from this hypothesis is that the ␣␥2 complex might exhibit a measurable accumulation in the ER. In fact several studies have now shown that the ER form of the ␣-chain is produced at significantly higher levels in cells transfected with both ␣-and ␥-chains compared with ␣-/␥-/␤-transfectants (4,66). The ␤-chain is well known to function in the amplification of Fc⑀RI surface expression, and it has been suggested that it may act as a chaperone for Fc⑀RI transport primarily because of its capacity to enhance post-translational Golgi processing of the ␣-chain (66).…”
Section: Discussionmentioning
confidence: 99%
“…One prediction from this hypothesis is that the ␣␥2 complex might exhibit a measurable accumulation in the ER. In fact several studies have now shown that the ER form of the ␣-chain is produced at significantly higher levels in cells transfected with both ␣-and ␥-chains compared with ␣-/␥-/␤-transfectants (4,66). The ␤-chain is well known to function in the amplification of Fc⑀RI surface expression, and it has been suggested that it may act as a chaperone for Fc⑀RI transport primarily because of its capacity to enhance post-translational Golgi processing of the ␣-chain (66).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was revealed that ␤-chain amplified degranulation and leukotriene secretion but suppressed cytokine production (12), indicating that ␤-chain regulates distinct intracellular signaling events in both positive and negative manners by the same molecule of itself. Furthermore, an alternative splice variant which encoded only an N-terminal portion of ␤-chain was found to be expressed in human mast cells (13). This truncation variant competed with full-length ␤ and prevented Fc RI surface expression by inhibiting ␣-chain maturation (13).…”
mentioning
confidence: 99%
“…Furthermore, an alternative splice variant which encoded only an N-terminal portion of ␤-chain was found to be expressed in human mast cells (13). This truncation variant competed with full-length ␤ and prevented Fc RI surface expression by inhibiting ␣-chain maturation (13). Because all of these findings indicate that ␤-chain is a fine regulator of Fc RI-mediated cell activation to precisely control the allergic reaction, elucidation of regulatory mechanisms of ␤-chain expression will make a meaningful contribution to medical intervention for allergy.…”
mentioning
confidence: 99%
“…Signals triggered by FcRβ-associated FcεRI were found to be of a higher intensity than signals triggered by FcεRI associated with FcRγ only (Dombrowicz et al, 1998). FcRβ also enhances IgE-induced allergic responses by up-regulating the surface expression of FcεRI (Donnadieu et al, 2003). Recently, however, FcRβ was found to generate ITAM-dependent negative signals.…”
Section: Fcrβmentioning
confidence: 99%